IMPACT OF 73RD CONSTITUTIONAL AMENDMENT ACT ON THE LOCAL SELFGOVERNMENT IN INDIA - Samaresh Chattaraj (Galaxy International Interdisciplinary Research Journal, 2021)
This paper seeks to examine the functional aspects of Panchayati Raj Institutions, especially in the aftermath of the 73rd constitutional Amendment. After a brief review of the history of local self government in the pre – and post independence India, an attempts is made to figure out the present system of the panchayat governance in India. The 73rd amendment give recognition and protection to local governments. It mainly aims to protect the poorer section of people from exploitation by making Gram Sabhas centers of self governance. It is the most progressive legislation for recognizing the traditional rights of the indigenous communities over the natural resources. It makes provisions for the reservation of seats at all the three levels in favor of women, the schedule castes, the schedule tribes and the other backward classes. This paper argues that despite the constitutional amendment to regenerate the PRIs there is still lack of genuine and strong political interest and bureaucratic support to fuel the institutions.The traditional factors rooted in the socioeconomic structure and political dynamics of the rural society continue to plague the working of these democratic institutions. It has been contended that there is need for another round of constitutional amendment coupled with continuous political and administrative support to ensure steady growth of the PRIs. The rise of civil society organizations which have started acting as watchdogs in some of the states. They are working not only for generating awareness among the stakeholders but also for organizing the villagers to assert their rights and in this respect the right to information has come as great soon.